Presupposition in The 2024 United States Presidential Debate - Salma, Najla Nazhifah; Heryono, Heri (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This study aims to analyze the types of presupposition and presupposition triggers in The United States Presidential Debate 2024. It focuses on identifying the types of presuppositions and the presupposition triggers used by the candidates during the debate. Utilizing a qualitative descriptive approach, data were collected from official debate transcripts and analyzed based on theories by Yule (1996) and Levinson (1983). The results show that existential, factive, lexical, and structural presuppositions frequently appear in the candidates’ utterances. These are primarily triggered by definite descriptions, factive verbs, change-of-state verbs, and interrogative structures. The findings indicate that candidates strategically employ presuppositions to present opinions as established facts, frame narratives persuasively, and subtly influence public perception. This study contributes to the understanding of political discourse by uncovering how language is used implicitly to construct meaning and persuade audiences in political settings.